IDENTIFIKASI POTENSI BAHAYA K3 DAN PENGENDALIAN RISIKO PADA KEGIATAN PEMBORAN DI BALAI DIKLAT TAMBANG BAWAH TANAH SAWAHLUNTO IDENTIFICATION OF POTENTIAL OHS HAZARDS AND RISK CONTROL IN DRILLING ACTIVITES IN THE SAWALUNTO UNDERGROUND MINING AND TRAINING CE - Muchtar Arifin; Taufan Fachsa; Amran Mulyadi; Sepriadi , Sepriadi (Jurnal Cakrawala Ilmiah, 2024)
OHS in mining activities is generally known as the Mining Occupational Health and Safety Management System (MOHS) which will regulate how and what forms of prevention and control both potential hazards or risks occur during mining activities. Drilling is one of the stages carried out before blasting activities. This is to obtain drilling fast, with the right position. The drilling, which was carried out at the Underground Mining Training Center, used a Jumbo drill and Jackleg machine. Risk identification is the process of identifying hazards, assessing risks and developing management strategies. The application of risk management has benefits including being able to guarantee business continuity by reducing the risk of every activity that contains a hazard, while the purpose of this study is to identify potential hazards and control the risk of work accidents for both workers and trainees at the Sawalunto Underground Mining Training Center.